Model komunikasi dan strategi kebijakan kesadaran anti korupsi / Gatut Priwidodo, Yustisia Ditya Sari ; editor, Th. Arie Prabawati - GATUT PRIWIDODO; Yustisia Ditya Sari; Arie Prabawati, Th. (Andi, 2017)
xiv, 114 hlm. : ilus. ; 23 cm